Doping High‐Mobility Donor–Acceptor Copolymer Semiconductors with an Organic Salt for High‐Performance Thermoelectric Materials. (16th January 2020) - Guo, Jing; Li, Guodong; Reith, Heiko; Jiang, Lang; Wang, Ming; Li, Yuhao; Wang, Xinhao; Zeng, Zebing; Zhao, Huaizhou; Lu, Xinhui; Schierning, Gabi; Nielsch, Kornelius; et al.
Abstract: Organic semiconductors (OSCs) are attractive for fabrication of thermoelectric devices with low cost, large area, low toxicity, and high flexibility. In order to achieve high‐performance organic thermoelectric devices (OTEs), it is essential to develop OSCs with high conductivity (σ ), large Seebeck coefficient ( S ), and low thermal conductivity (κ ). It is equally important to explore efficient dopants matching the need of thermoelectric devices. The thermoelectric performance of a high‐mobility donor–acceptor (D–A) polymer semiconductor, which is doped by an organic salt, is studied. Both a high p‐type electrical conductivity approaching 4 S cm −1 and an excellent power factor ( PF ) of 7 µW K −2 m −1 are obtained, which are among the highest reported values for polymer semiconductors. Temperature‐dependent conductivity, Seebeck coefficient and power factor of the doped materials are systematically investigated. Detailed analysis on the results of thermoelectric measurements has revealed a hopping transport in the materials, which verifies the empirical relationship:  S  ∝ σ −1/4 and PF  ∝ σ 1/2 . The results demonstrate that D–A copolymer semiconductors with proper combination of dopants have great potential for fabricating high‐performance thermoelectric devices. Abstract : An organic salt is employed to efficiently p‐dope a high‐mobility donor–acceptor (D–A) copolymer semiconductor for fabrication of thermoelectric (TE) devices, which yields a high conductivity of over 4 S cm −1 and a power factor of 7 µW K −2 m −1 . This work provides new opportunities for development and application of organic thermoelectric devices based on high‐mobility organic semiconductors.